Reviewing two-phase flow modeling in membrane processes through computational fluid dynamics - Lam, W. Y.; Liang, Y. Y.; Ng, K. C.; Li, M.; A. L., Ahmad; Fimbres Weihs, G. A. (Elsevier Ltd, 2025)
Over the past two decades, the use of computational fluid dynamics (CFD) has witnessed widespread adoption as a pivotal approach for analyzing two-phase dynamics within membrane systems. The two-phase system typically arises from gas injection, aimed at improving membrane separation efficiency through improved mixing by mitigating the impact of concentration polarization (CP) and membrane fouling. While numerous CFD studies have contributed to this domain, an exhaustive and critical overview of the contemporary state of this field remains absent. To address this gap, this review comprehensively synthesizes the existing body of knowledge, outlining the theoretical underpinnings of the two-phase flow membrane system, accompanied by proper choice of CFD boundary conditions. In addition, this review investigates the extent to which current two-phase CFD models align with experimental findings, shedding light on applicability of these simulations in practical scenarios, while explores the current state-of-the-art of CFD modeling to capture the intricate interplay of gas injection dynamics and membrane behavior. Finally, research opportunities within CFD modeling of two-phase dynamics for membrane systems are outlined.